Bringing a Public Library to Boston's Chinatown: How to build the Political Will. - Rausch, Tali.; Fitzpatrick, Kara.; Bell, Samuel.; Liu, Ying. (Tufts University. Tisch Library., 2018)
2005 M.A. in Urban and Environmental Policy and Planning Field Project. Client: The Chinese Progressive Association, Boston, MA.